![image](https://tex.z-dn.net/?f=x%5E%7B3%5Clg+x%7D+%3D+10x%5E2%5C%5C%5C%5C%0A10+%3D+x%5E%7B%5Clog_%7Bx%7D+10%7D%5C%5C%5C%5C%0Ax%5E%7B3%5Clg+x%7D+%3D+x%5E%7B%5Clog_%7Bx%7D+10%7Dx%5E2%5C%5C%5C%5C%0Ax%5E%7B3%5Clg+x%7D+%3D+x%5E%7B%5Clog_%7Bx%7D+10+%2B+2%7D%5C%5C%5C%5C%0A3%5Clg+x+%3D+%5Clog_%7Bx%7D10+%2B+2+%5C+%7C+%5C+%2A+%5Clg+x%2C+%5C+x+%3E+0%2C+%5C+x+%5Cne+1%5C%5C%5C%5C%0A3%5Clg%5E2+x+%3D+1+%2B+2%5Clg+x%5C%5C%5C%5C%0A3%5Clg%5E2+x+-+2%5Clg+x+-+1+%3D+0%2C+%5C+t+%3D+%5Clg+x)
0, \ x \ne 1\\\\
3\lg^2 x = 1 + 2\lg x\\\\
3\lg^2 x - 2\lg x - 1 = 0, \ t = \lg x" alt="x^{3\lg x} = 10x^2\\\\
10 = x^{\log_{x} 10}\\\\
x^{3\lg x} = x^{\log_{x} 10}x^2\\\\
x^{3\lg x} = x^{\log_{x} 10 + 2}\\\\
3\lg x = \log_{x}10 + 2 \ | \ * \lg x, \ x > 0, \ x \ne 1\\\\
3\lg^2 x = 1 + 2\lg x\\\\
3\lg^2 x - 2\lg x - 1 = 0, \ t = \lg x" align="absmiddle" class="latex-formula">